Battle discussion method to increase student involvement in theoretical courses - Yofita Sandra; Syerlie Annisa; Dini Faisal; Anggun Anugrah (Institut Seni Indonesia Surakarta, 2026)
The primary objective of higher education is to develop students’ transversal skills through critical thinking and analytical reflection. The purpose of this study is to illustrate how lecturers use the dialectical technique named battle discussion to help students strengthen their critical thinking skills. A mixed method was used to conduct the study. Thirty students were chosen randomly from courses in Nusantara Fine Arts History as quantitative data. Throughout the learning process, structured field records were used to collect qualitative data. Field notes were used to analyse qualitative data, whereas descriptive and percentage analysis were employed for quantitative data. The study's findings demonstrated that the battle discussion method improved students' critical thinking skills, increased their mastery of the subject, and increased their engagement in class. The overall mean score for group engagement in the Battle Discussion was 5.25 out of 7.00 (75% involvement), which generally falls into the High involvement category. However, a deeper examination of the data reveals a high standard deviation (SD = 2.01), indicating significant data heterogeneity and a noticeable disparity in participation across the ten groups. These findings prove that the battle discussion method can be used as an alternative to enhance students' ability to think critically, and in the future, more comprehensive development is needed on aspects that can be transformed from theory to practice.